(3JdbjM aghe Cgd GdCKQ aj Yjhf GdJGQjN hGdSjQs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi EMSGfg hZaVGdg s
(3BNQgG (B:s
(3GdcdGe Ydi GdWHbI GdKGdKI YTQI YfO QCS GdYTQjf hGdNeSeGFI hcGf GdNdjaI GdeSJQTO HGddg s
(3fSNI YdjgG bQGAGJ jhSa Hf eSYhO GdSheQi hYdi Hf eMeO Hf Ydi GdQYjfi dGCfOdSi GdZQJGWi hYdjgG NWgeGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B316 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B157 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B520s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B98 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(2968) s
Keywords: (3GdJGQjNs